Sofosbuvir plus Ribavirin is effective for HCV elimination in people living with HIV from rural area of China - Liyu Chen (Scientific Reports, 2021)
Abstract People living with HIV (PLWH) bear higher prevalence of HCV coinfection. An accessible directly acting antivirals regimen with less drug–drug interaction with antiretroviral therapy (ART) is urgently needed in source limited regions. We aimed to assess the efficacy and safety of SOF + RBV for 24 weeks regimen in HIV–HCV coinfected patients in Liangshan Prefecture, China. PLWH under ART from China’s national free antiretroviral treatment project (CNFATP) and diagnosed with treatment-naïve HCV infection were enrolled. SOF + RBV was administrated for 24 weeks and patients were followed for ≥ 12 weeks. The efficacy and safety were analyzed and related factors were explored. 58 patients completed 24 weeks of SOF + RBV and had all tests done. Genotype prevalence in this population was G3 44.8% (n = 26), G6 31.0% (n = 18) and G1 17.2% (n = 10) respectively. 52/58 (89.7%) patients achieved SVR12 while 10.3% experienced therapeutic failure. However, SVR12 was neither significantly different between groups of different gender, age, transmission routines, CD4+ cell count, HIV infection duration, ART duration and HBsAg prevalence nor influenced by HCV viral load, genotypes and hepatic stiffness. The regimen was well-tolerated without any serious AEs or AEs leading to treatment adjustment or discontinuation reported. PLWH in Liangshan showed a high prevalence of HCV coinfection with GT3 and GT6 as the most frequent genotypes. SOF + RBV for 24 weeks could achieve good SVR12 in this population and was well-tolerated. It has great potential to be generalized in coinfected population in source-limited regions.